Taxonomic identity of Utricularia malabarica (Lentibulariaceae), a species endemic to the lateritic plateaus of the Western Ghats, India - Kolte , R. R.; Deshpande , A. S.; Pillai , P. M.; Janarthanam, M. K. (Rheedea, 2019)
Utricularia malabarica Janarth. & A.N. Henry, previously considered conspecific to U. praeterita P. Taylor, is reinstated here based on morphological characters. The diagnostic characters to separate them include the nature of pedicel, shape and lobation of lower lip of corolla and features of spur. Details of habitat, ecology, phenology, photographic and analytical evidences and notes are presented in this paper.